MOBILITY AND POLICY IMPACT MODELS AND SIMULATIONS IN CASES OF SPREAD OF COVID-19 - Aini, Wirdatul
The SARS-COV-2 infection, known as Coronavirus-2019 (COVID-19), was first detected in Wuhan, China in early 2020. Within two months, this COVID-19 has spread in more than 114 countries. Until now, discussions on the topic of the spread of COVID-19 are still developing in many scientific disciplines, including mathematics. When viewed from the aspect of mobility, human movement is an important factor in the spread of COVID-19, especially when millions of people travel ahead of Eid al-Fitr. In this study, a mathematical model of the spread of COVID-19 in the population will be constructed which describes the dynamics of the disease using data in the Jabodetabek (Jakarta-Bogor-Depok-Tangerang-Bekasi) and Baraya (Bandung Raya) regions, as well as understanding the effect of interregional mass exodus on cases active COVID-19 in a mathematical perspective. This research builds a multi-region SIQRD (Susceptible-Infected-Quarantined- Recovered-Death) model that accommodates direct movement of a person from one region to another. The mathematical model that is constructed will involve situations and conditions starting from the initial phase of the pandemic and the effect of mobility on the Eid homecoming situation in 2021. The main objective of this research is to construct a function that can reflect the phenomenon of back and forth flow which is a distinctive culture of the people in Indonesia. The construction of this function was chosen using the Dawson function approach with modified assumptions that reflect mobility during the Eid season in Indonesia.